Energy-optimal Speed Trajectories of Electric City Buses - Qiu, Johanna (International Journal of Electric Power and Energy Studies, 2025)
Electric vehicles are a key technology in the shift towards sustainable transportation. However, significant improvements can be made in terms of their energy efficiency, and driving style plays a major role. Speed trajectories can be more easily implemented with city buses; therefore, this investigation aims to find energy-optimal speed trajectories between bus stops of a given distance. While many studies have been conducted on small passenger vehicles, research on the trip characteristics of buses is more lacking. Three-segment speed trajectories were evaluated in this investigation, using closed-form equations derived from integrating battery power. Results show that higher average velocities correlate with higher energy consumption, and speed trajectories with larger values of acceleration and deceleration have lower energy consumption and are more energy efficient.